Explosion of limb muscles on the ability of Mae Geri Chudan Karateka Lemkari Dojo Bato Pariaman City - zulman Zulman; Arie Asnaldi (Universitas Negeri Padang, 2019)
The purpose of this research is to examine the effect of leg muscle explosive power exercises to increase the ability of mae geri chudan karateka son of Lemkari Dojo Bato Pariaman city. Type of this research is pre experimental with one group design pre-test and post test. The population of this research is 25 peoples. This sampling was done by using purposive sampling technique, so that got the sample as many as 14 peoples who are given of muscle leg muscle as many as 16 times for training. The technique of collecting data is using by mae geri chudan test instrument with validity and reliability of instrument 0,98 and 0,97. The data analysis uses the t-test formula which a result is used to test of hypotesis. From the data analysis obtained tcount (6.75) > ttable (1.771), so the hypotesis was accepted. Thus it can be summed up the exercise by using the explosive power tension training method to improve the ability of mae geri chudan karateka son Lemkari Dojo Bato Pariaman city.